Changing paradigms in oncology: Toward noncytotoxic treatments for advanced gliomas. Issue 9 (16th June 2022) - von Knebel Doeberitz, Nikolaus; Paech, Daniel; Sturm, Dominik; Pusch, Stefan; Turcan, Sevin; Saunthararajah, Yogen
Abstract: Glial‐lineage malignancies (gliomas) recurrently mutate and/or delete the master regulators of apoptosis p53 and/or p16/CDKN2A, undermining apoptosis‐intending (cytotoxic) treatments. By contrast to disrupted p53/p16, glioma cells are live‐wired with the master transcription factor circuits that specify and drive glial lineage fates: these transcription factors activate early‐glial and replication programs as expected, but fail in their other usual function of forcing onward glial lineage‐maturation—late‐glial genes have constitutively "closed" chromatin requiring chromatin‐remodeling for activation—glioma‐genesis disrupts several epigenetic components needed to perform this work, and simultaneously amplifies repressing epigenetic machinery instead. Pharmacologic inhibition of repressing epigenetic enzymes thus allows activation of late‐glial genes and terminates glioma self‐replication (self‐replication = replication without lineage‐maturation), independent of p53/p16/apoptosis. Lineage‐specifying master transcription factors therefore contrast with p53/p16 in being enriched in self‐replicating glioma cells, reveal a cause‐effect relationship between aberrant epigenetic repression of late‐lineage programs and malignant self‐replication, and point to specific epigenetic targets for noncytotoxic glioma‐therapy. Abstract :